2000
DOI: 10.1007/bf03190074
|View full text |Cite
|
Sign up to set email alerts
|

Effect of food on the pharmacodynamics and pharmacokinetics of atorvastatin, an inhibitor of HMG-CoA reductase

Abstract: The pharmacodynamics and pharmacokinetics of atorvastatin, an HMG-CoA reductase inhibitor, were characterized in 16 healthy subjects following administration of 10 mg atorvastatin tablets with, or 3 h after, evening meals for 15 days in an open-label, randomized, 2-way crossover study. Atorvastatin was well tolerated. Atorvastatin administration with evening meals resulted in 25.2% lower mean Cmax and 29.8% longer mean tmax values relative to administration after meals. The mean AUC(0-24) value was 8.6% lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 6 publications
2
18
0
Order By: Relevance
“…However, this decrease is not considered clinically relevant, as similar decreases associated with food intake and nighttime dosing have been observed, while efficacy was maintained when these other factors were present (19)(20)(21). Extensive meta-analysis indicated that the efficacy of statins correlates with total daily exposure rather than with peak exposure.…”
Section: Discussionmentioning
confidence: 99%
“…However, this decrease is not considered clinically relevant, as similar decreases associated with food intake and nighttime dosing have been observed, while efficacy was maintained when these other factors were present (19)(20)(21). Extensive meta-analysis indicated that the efficacy of statins correlates with total daily exposure rather than with peak exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The published data on atorvastatin show that a reduction in LDL-C associated with the administration of atorvastatin is more highly correlated with the total daily atorvastatin dose rather than with the measurement of peak atorvastatin exposure ( C max ). 1,2,3,4 …”
Section: Discussionmentioning
confidence: 99%
“…1,2,3,4 Reductions in atorvastatin C max are not associated with changes in LDL-C lowering efficacy. 1,5,6 The biological processes governing the changes in LDL-C occur over a range of weeks to months, whereas plasma concentrations of atorvastatin peak within an hour after dosing.…”
mentioning
confidence: 95%
“…The bioavailability of pravastatin was reduced by 31% when taken with food, but its lipid-lowering efficacy was unchanged [96]. For atorvastatin and fluvastatin, the bioavailability and effects were not affected by food intake [97][98][99]. GFJ is a clinically important beverage because GFJ constituents inhibit intestinal CYP3A4 [100,101].…”
Section: Drug--food Interactions With Cypsmentioning
confidence: 99%